Guiding electron transfer for selective C2H6 photoproduction from CO2 - Xu, Jingyi; Chong, Meichi; Li, Wenting; Zhu, Enwei; Jin, Hongqiang; Liu, Liping; Ren, Yuehong; Zhu, Yongfa (Chem, 2025)
Unguided electron transfer presents challenges for selectively photo-reducing carbon dioxide (CO2) into C2 products. We constructed continuous inter- and intra-component electric fields within photocatalysts by in situ chemical encapsulation. The dual-tandem electric fields facilitate charge separation and transfer photogenerated electrons accurately toward Cu2+-Cu+ sites for C–C coupling. We tracked the electron transport, observing directional electron migration between contacted heterostructure atoms, ligand carbon atoms, and Cu2+-Cu+ centers. The as-synthesized photocatalyst manifests a remarkable ethane (C2H6) production rate of 16.3 μmol g−1 h−1, a high electron selectivity of 64.4% for C2H6, and a stable electron consumption yield of 354.6 μmol g−1 h−1 in water vapor. These represent one of the best performances for CO2 photoreduction. This work promotes charge separation and manages precise control over electron migration via tandem built-in electric fields, opening a new prospect for selective CO2 photoreduction into high-value chemicals. [Display omitted] •Electron transfer is guided via dual-tandem electric fields toward Cu+-Cu2+•The transferring paths of electrons are unveiled from atom to atom•Remarkable C2H6 photoproduction rates and high selectivity are achieved Solar energy is a plentiful and clean source of energy. Utilizing photocatalytic technology to convert water and CO2 into fuel shows great potential in terms of cost-effectiveness. However, current photoreduction processes often result in low-value C1 molecules like CO and CH4 due to unguided carrier transfer. To address this, we developed an encapsulation photocatalyst with tandem built-in electric fields. These sequential fields not only promote charge separation but also enable precise control over photogenerated electron transfer. By concentrating electrons on the Cu2+-Cu+ site, we successfully achieved the selective photosynthesis of ethane. This work introduces a pioneering and transferable idea for converting CO2 into high-value-added products, shedding light on controllable chemical conversion and precise photocatalysis. Current photocatalytic CO2 reduction commonly results in low-value C1 products due to unguided carrier transfer. This work developed an encapsulation photocatalyst with tandem built-in electric fields. These sequential fields not only promote charge separation but also enable precise control over photogenerated electron transfer. By concentrating electrons on the Cu2+-Cu+ site, we successfully achieved the selective photosynthesis of ethane.